What is new on cardiac troponin degradation? - Mair, Johannes (Journal of Laboratory and Precision Medicine, 2017)
Cardiac troponin I (cTnI) and cardiac troponin T (cTnT) are nowadays the criterion biomarkers for the laboratory diagnosis of acute and chronic myocardial injury due to their very high sensitivities and specificities (1). However, still many aspects of their intramyocardial degradation, their tissue release, and their degradation within and elimination from the human circulation are still incompletely understood. In a recently published manuscript Katrukha et al. (2) reported an important novel finding, i.e., degradation of human cTnT by thrombin, the most abundant coagulation enzyme. This editorial aims to give an update on what is known about degradation of human cTnI and cTnT and also points to gaps of current knowledge.